2019
DOI: 10.1111/pce.13603
|View full text |Cite
|
Sign up to set email alerts
|

A human pathogenic bacterium Shigella proliferates in plants through adoption of type III effectors for shigellosis

Abstract: Shigella, which infects primates, can be transmitted via fresh vegetables; however, its molecular interactions with plants have not been elucidated. Here, we show that four Shigella strains, Shigella boydii, Shigella sonnei, Shigella flexneri 2a, and S. flexneri 5a, proliferate at different levels in Arabidopsis thaliana. Microscopic studies revealed that these bacteria were present inside leaves and damaged plant cells. Green fluorescent protein (GFP)‐tagged S. boydii and S. flexneri 5a colonized leaves only,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 75 publications
(105 reference statements)
0
19
0
Order By: Relevance
“…Protection against intracellular pathogens requires a dominant Th1-type immunity [52]. This has been demonstrated with S. Typhi, an intracellular bacterium, which after immunization using alum adjuvant and GroEL, predominantly induced Th2 types response associated with the lowest protection levels [29].…”
Section: Discussionmentioning
confidence: 98%
“…Protection against intracellular pathogens requires a dominant Th1-type immunity [52]. This has been demonstrated with S. Typhi, an intracellular bacterium, which after immunization using alum adjuvant and GroEL, predominantly induced Th2 types response associated with the lowest protection levels [29].…”
Section: Discussionmentioning
confidence: 98%
“…A study has demonstrated that some strains of bacteria belonging to the genus Shigella, that cause shigellosis (severe intestinal infection), can survive and multiply in damaged plant cells, roots, and leaves of A. thaliana (Jo et al 2019). These bacteria proliferate in plants by adoption of type III effectors for shigellosis.…”
Section: Occurrence Of Human Pathogenic Bacteria In Plant Environmentmentioning
confidence: 99%
“…P. aeruginosa utilizes common pathogenicity factors (toxA, plcS and gacA) in Arabidopsis thaliana and mouse (Rahme et al, 1995). Recently, humanpathogenic Shigella species were shown to produce type III effector proteins and interact with plant target proteins as well as being involved in human and animal pathogenesis (Jo et al, 2019).…”
Section: Molecular Mechanisms Of Pathogenesis Involved In Cross-kingdmentioning
confidence: 99%
“…These include some of the species in the Pantoea, Burkholderia, Rhizobium and Pseudomonas genera, all of which can cause animal disease despite being primarily known as plant disease agents. Similarly, some species of Salmonella (Schikora et al, 2008;Barak et al, 2011), Enterobacter (Nishijima et al, 2007), Shigella (Jo et al, 2019) and Enterococcus (Jha et al, 2005), mainly considered to be animal pathogens, are also capable of causing infections in plant hosts. With a few exceptions, clinical isolates of phytopathogens have largely been obtained from immunocompromised or postsurgical patients, or from post-traumatic patients (i.e.…”
Section: Introductionmentioning
confidence: 99%